Early Christian spiritualties of sin and forgiveness according to 1 John - Van der Merwe, Dirk (HTS teologiese studies, 2014)
The article attempts to investigate the possible lived experiences created by this text. The text revolves around the experience of fellowship with God (1:6, 7) who is characterised as ‘light’. For the author of 1 John, sin disrupts this fellowship. He creates an awareness and a ‘spirituality of sin and guilt’ in the lives of his readers through the use of the experiential metaphor of darkness in a dialectic combination with light and the two false negations ‘do not have sin’ (sin as a noun) and ‘do not sin’ (sin as a verb). This fellowship is re-established through living in the light: the confession, forgiveness and expiation of sin. The author creates a spirituality of confession, forgiveness and expiation of sin through descriptive cultic (blood of Jesus and expiation), forensic (paraclete), atypical (cleans, expiation, paraclete) and all-inclusive (all [twice], whole, anyone) language. Thus, in his rhetoric, the author uses metaphor, dialectic, sacrificial, forensic, atypical and all-inclusive language to facilitate a variety of ‘lived experiences’ within his readers. Firstly, he wants them to feel guilty about their sins and consequently, after they have confessed their sins, to strengthen their faith. Secondly, he wants to encourage them to believe that they can experience the forgiveness of their sins and, by doing so, know that they have eternal life (5:13) and can experience fellowship with God and, mutually, with one another.